Case report: A novel mutation of RecQ-like helicase 5 in a Chinese family with early myocardial infarction, coronary artery disease, and stroke hemiplegia - Tang, Yi; Wang, Qian; Zhang, Wei-Kai; Liu, Yu-Xing; Zheng, Zhao-Fen; Fan, Liang-Liang; Liu, Lv; He, Jin (Frontiers in Genetics, 2023)
Background: Myocardial infarction (MI) is one type of serve coronary artery disease (CAD) which can lead to heart failure and sudden cardiac death. The prevalence of heart failure in the world is estimated at 1-2%, of which ~60% of cases are the consequence of MI as primary cause. At present, several disease-causing genes have been identified may be responsible for MI, such as Autophagy Related 16 Like 1 (ATG16L1), RecQ Like Helicase 5 (RECQL5). Methods: In this study, we enrolled a Chinese family with MI, CAD, and stroke hemiplegia. Whole exome sequencing was applied to analyze the genetic lesion of the proband. Sanger sequencing was used to validate the candidate mutation in five family members and 200 local control cohorts. Results: After data filtering, we detected a novel mutation (NM_004259: c.1247T>C/ p.I416T) of RECQL5 in the proband. Sanger sequencing further validated that the novel mutation was exist in the affected individuals including the proband’s young sister and her mother and absent in the other health family members and 200 local control cohorts. Further bioinformatics analysis confirmed that the novel mutation, located in a highly evolutionarily conserved site, was predicted to be deleterious and may change the hydrophobic surface area and aliphatic index of RECQL5. Conclusion: Here, we may report the second mutation (NM_004259: c.1247T>C/ p.I416T) of RECQL5 underling MI and CAD by whole exome sequencing. Our study expanded the spectrum of RECQL5 mutations and contributed to genetic diagnosis and counseling of MI and CAD.